SNR improvement in self-heterodyne detection Brillouin optical time domain reflectometer using Golay pulse codes - 李永倩;李晓娟;范寒柏;安琪;张立欣 (Optoelectronics letters, 2017)
The application of Golay pulse coding technique in spontaneous Brillouin-based distributed temperature sensor based on self-heterodyne detection of Rayleigh and Brillouin scattering is theoretically and experimentally analyzed. The enhancement of system signal to noise ratio（SNR） and reduction of temperature measurement error provided by coding are characterized. By using 16-bit Golay coding, SNR can be improved by about 2.77 d B, and temperature measurement error of the 100 m heated fiber is reduced from 1.4 °C to 0.5 °C with a spatial resolution of 13 m. The results are believed to be beneficial for the performance improvement of self-heterodyne detection Brillouin optical time domain reflectometer.